Educational Videos in Regional Languages as Health Promotion Media for Compliance with Controls and Taking Medication among Hypertension Patients: Video Edukasi dalam Bahasa Daerah sebagai Media Promosi Kesehatan untuk Kepatuhan Kontrol dan Minum Obat pada Pasien Hipertensi - Sutrisno; Suparman; Tri Gunarto, Sugito; Ardiana, Anisah; Widodo Eko Putra, Wisnu (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2024)
The therapy process for hypertensive patients includes several aspects, one of which is treatment by taking antihypertensive medication, which must be done regularly according to the doctor's recommendations. Compliance with carrying out routine controls and taking medication in hypertensive patients is a very important part of treatment, because this compliance aims to reduce the risk of complications such as cardiovascular disease, cerebrovascular disease and kidney disorders. Therefore, in the process of treating hypertensive patients, discipline is very necessary to carry out regular health control and adhere to the medication schedule. To increase this compliance, video-based educational media using regional languages ​​is an effective approach. Regional language educational videos make it easier for patients to understand the health messages conveyed, so that patients can better understand the importance of following treatment rules consistently. Through this educational media, it is hoped that patient compliance with control and taking medication can increase, so that they can achieve success in managing hypertension conditions and preventing further complications. The aim of this Agronursing Internship Management Practice activity is to develop health promotion media in the form of regional language educational videos that focus on compliance in controlling and taking medication in hypertensive patients. This practice uses a questionnaire method to collect data and assess the effectiveness of the educational video in increasing patient awareness and compliance with the treatment they have to undergo.